Effect and Mechanism of VR Exercise Therapy on Improving Physical Function in Elderly Patients with Parkinson's Disease - Xiaodong Liao; Luo, Jiong (Ilmu Inovasi Nusantara, 2025)
Parkinson's disease (PD) is a neurodegenerative disorder primarily affecting the elderly, leading to significant impairments in mobility, limb dysfunction, and an increased risk of falls, while also deteriorating emotional, cognitive, and sleep functions, ultimately reducing the overall quality of life. Despite pharmacological treatments, non-drug interventions are essential to address these multidimensional challenges. Virtual reality (VR) exercise therapy, an interactive approach combining exercise and cognitive stimulation, has emerged as a potential non-pharmacological intervention for PD. This review aims to evaluate the impact of VR exercise therapy on the physical and cognitive functions of PD patients. A systematic search of databases, including PubMed, Web of Science, CNKI, and Google Scholar, was conducted to identify relevant studies examining the effects of VR therapy on PD patients. The review found that the pathogenesis of PD, characterized by the degeneration of dopaminergic neurons in the substantia nigra, can be partially addressed by VR therapy. VR exercise therapy enhances motor function, improves cognitive abilities, and positively affects specific physiological indicators. Furthermore, VR therapy’s interactive nature allows for tailored exercise regimens, which help in muscle and nerve function improvement. The results indicate that VR exercise therapy can be an effective intervention for improving motor and cognitive functions in PD patients. However, long-term engagement is essential to maintain its therapeutic benefits. Based on the findings, we recommend that healthcare providers consider integrating VR exercise therapy into PD treatment plans as part of a comprehensive, non-pharmacological approach, while encouraging sustained usage for lasting improvements